Assessing the Attractiveness of the Investment Market in the Republic of Armenia - Hovnanyan, Levon; Tadevosyan, Zoya (ՀՀ ԳԱԱ)
Due to the global financial and economic crisis that began in 2008, the Armenian economy found itself in a period of deep decline and, naturally, as expected, both domestic and foreign investment fell sharply. In the post-crisis years, as the economy gradually began to emerge from the crisis and gradually recover from the positive dynamics of macroeconomic indicators, however, no significant increase in investment flows was recorded; the investment market is still characterized by low activity. 2008 թ-ին սկիզբ առած համաշխարհային ֆինանսատնտեսական ճգնաժամի հետևանքով ՀՀ տնտեսությունը հայտնվեց բավականին խորը անկման շրջանում ու, բնականաբար, ինչպես և սպասվում էր, թե՛ տեղական, թե՛ օտարերկրյա ներդրումների ծավալները կտրուկ կրճատվեցին: Հետճգնաժամային տարիներին, թեև տնտեսությունն աստիճանաբար սկսեց դուրս գալ ճգնաժամից և հետզհետե վերականգնել մակրոտնտեսական ցուցանիշների դրական դինամիկան, այնուամենայնիվ ներդրումների հոսքերի էական աճ չարձանագրվեց և ներդրումային շուկան մինչ օրս բնութագրվում է ցածր ակտիվությամբ: Из-за мирового финансово-экономического кризиса, начавшегося в 2008 году, экономика Армении оказалась в периоде глубокого спада и, естественно, как и ожидалось, резко сократились как внутренние, так и иностранные инвестиции. В посткризисные годы, по мере постепенного выхода экономики из кризиса и постепенного восстановления положительной динамики макроэко-номических показателей, однако, существенного увеличения инвестиционных потоков не фиксировалось, инвестиционный рынок по-прежнему характеризуется низкой активностью.
Keywords: Social and Humanitarian Sciences